Molding Nineteenth-century Girls in the Cape Colony into Respectable Christian Women. Issue 2 (1st July 2019) - Dillenburg, Elizabeth
Abstract : S. E. Duff. 2015. Changing Childhoods in the Cape Colony: Dutch Reformed Church Evangelicalism and Colonial Childhoods, 1860–1895. Basingstoke, UK: Palgrave Macmillan. In Changing Childhoods in the Cape Colony: Dutch Reformed Church Evangelicalism and Colonial Childhoods, 1860–1895 (hereafter Changing Childhoods), S. E. Duff explores shifting notions of childhood and, more specifically, the emergence of new ideas about white childhood in the Cape Colony, South Africa, during the late nineteenth century by examining various efforts to convert and educate children, especially poor white children, and improve their welfare. As indicated in the title, Changing Childhoods draws attention to the multiplicity of experiences of children who existed alongside each other in the Cape Colony and how they were shaped by a variety of factors, including religion, location, class, race, and gender. While many histories of childhood elide the experiences of boys and girls, Duff pays careful attention to the different constructions of girlhood and boyhood and how gender shaped the lives of boys and girls, men and women. Throughout the book, girls appear not as passive observers but as complex agents shaping and participating in broader social, political, cultural, and economic transformations in the Cape.